Radical cystectomy (bladder removal) against intravesical BCG immunotherapy for high-risk non-muscle invasive bladder cancer (BRAVO): a protocol for a randomised controlled feasibility study. Issue 8 (11th August 2017) - Oughton, Jamie B; Poad, Heather; Twiddy, Maureen; Collinson, Michelle; Hiley, Victoria; Gordon, Kathryn; Johnson, Mark; Jain, Sunjay; Noon, Aidan P; Chahal, Rohit; Simms, Matt; Dooldeniya, Mohantha; et al.
Abstract : Introduction: High-risk non-muscle invasive bladder cancer (HRNMIBC) is a heterogeneous disease that can be difficult to predict. While around 25% of cancers progress to invasion and metastases, the remaining majority of tumours remain within the bladder. It is uncertain whether patients with HRNMIBC are better treated with intravesical maintenance BCG (mBCG) immunotherapy or primary radical cystectomy (RC). A definitive randomised controlled trial (RCT) is needed to compare these two different treatments but may be difficult to recruit to and has not been attempted to date. Before undertaking such an RCT, it is important to understand whether such a comparison is possible and how best to achieve it. Methods and analysis: BRAVO is a multi-centre, parallel-group, mixed-methods, individually randomised, controlled, feasibility study for patients with HRNMIBC. Participants will be randomised to receive either mBCG immunotherapy or RC. The primary objective is to assess the feasibility and acceptability of performing the definitive phase III trial via estimation of eligibility and recruitment rates, assessing uptake of allocated treatment and compliance with mBCG, determining quality-of-life questionnaire completion rates and exploring reasons expressed by patients for declining recruitment into the study. We aim to recruit 60 participants from six centres in the UK. Surgical trials with disparate treatment options find recruitment challenging from both the patient and clinician perspective. By building on the experiences of other similar trials through implementing a comprehensive training package aimed at clinicians to address these challenges (qualitative substudy), we hope that we can demonstrate that a phase III trial is feasible. Ethics and dissemination: The study has ethical approval (16/YH/0268). Findings will be made available to patients, clinicians, the funders and the National Health Service through traditional publishing and social media. Trial registration number: ISRCTN12509361; Pre results.